What a difference a mentor can make - O’Brien, Judith (New Zealand Science Review, 2014)
What will motivate you to get up each morning and go to work? This is one of the questions I raise with students when discussing programme choices and the careers they may lead to. For me the answer to that question is having the opportunity to contribute to good decision making by the staff and students I work with in the School of Biological Sciences (SBS) at the University of Auckland.